(untitled) (LEGAL DIALOGICA, 2025)
The purpose of this research is to examine how the policy of chemical castration is regulated within the Indonesian legal framework and to analyze the implementation of chemical castration punishment in accordance with the principles of justice and human rights based on Indonesian positive law. The research method employed in this study is normative legal research through a literature review. The data analysis used is qualitative analysis..The findings of the research indicate that the policy on chemical castration in Indonesia, as regulated under Law Number 17 of 2016, is aimed at protecting children from sexual violence and preventing recidivism, grounded in the philosophical foundations of retribution, deterrence, and victim protection. However, this policy has sparked debates concerning human rights, particularly in relation to physical integrity and bodily autonomy. Moreover, its implementation poses several challenges, such as the need for strict medical supervision and the necessity of psychological rehabilitation for offenders. While chemical castration may reduce the sexual drive of offenders, its effectiveness in preventing further sexual crimes largely depends on a comprehensive rehabilitation system and consistent post-punishment monitoring. The recommendation of this research is that the application of chemical castration punishment should be carried out strictly, proportionally, transparently, and non-discriminatorily, while ensuring the physical and mental integrity of the offender in accordance with the principles of justice and human rights standards. Abstrak: Tujuan dilakukannya penelitian ini adalah untuk mengetahui kebijakan kebiri kimia diatur dalam peraturan perundang-undangan di Indonesia dan Untuk mengetahui penerapan hukuman kebiri kimia sesuai dengan prinsip keadilan dan hak asasi manusia berdasarkan hukum positif Indonesia. Metode penelitian yang digunakan di dalam penelitian ini adalah metode penelitian hukum normatif dengan studi kepustakaan. Analisis data yang digunakan adalah analisis data kualitatif, Hasil penelitian menunjukkan bahwa Kebijakan kebiri kimia di Indonesia, yang diatur dalam Undang-Undang Nomor 17 Tahun 2016, bertujuan untuk melindungi anak dari kekerasan seksual dan mencegah residivisme dengan dasar filosofis retribusi, pencegahan, dan perlindungan korban. Namun, kebijakan ini menimbulkan perdebatan terkait hak asasi manusia, terutama mengenai integritas fisik dan kebebasan tubuh, serta tantangan dalam penerapannya, seperti pengawasan medis yang ketat dan kebutuhan rehabilitasi psikologis bagi pelaku. Meskipun dapat menurunkan dorongan seksual pelaku, efektivitas kebiri kimia dalam mencegah kejahatan seksual lebih lanjut sangat bergantung pada sistem rehabilitasi yang menyeluruh dan pemantauan pasca-hukuman. Rekomendasi dalam penelitian ini adalah penerapan hukuman kebiri kimia harus dilakukan secara ketat, proporsional, transparan, dan tidak diskriminatif, serta menjamin integritas fisik dan mental pelaku sesuai dengan prinsip keadilan dan standar hak asasi manusia.